Experience of the Endoscopists Matters in Endoscopic Retrograde Cholangiopancreatography in Billroth II Gastrectomy Patients - Erkan Caglar; Deniz Atasoy; Mukaddes Tozlu; Engin Altınkaya; Serkan Dogan; Hakan Senturk (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Altered anatomy is a challenge in endoscopic retrograde cholangiopancreatography (ERCP) for patients with Billroth II anastomosis. In this study, we investigated the overall success and role of endoscopist experience. Methods Data of patients who underwent ERCP between 2014 and 2018 after a previous Billroth II operation were retrieved retrospectively from 2 tertiary ERCP centers. The procedures were performed by 2 endoscopists with different levels of experience. Clinical success was defined as extraction of the stone, placement of a stent through a malignant stricture, and clinical and laboratory improvements in patients. Result Seventy-five patients were included. The technical success rate was 83% for the experienced endoscopist and 75% for the inexperienced endoscopist (p=0.46). The mean (±standard deviation) procedure time was 23.8±5.7 min for the experienced endoscopist and 40.68±6.07 min for the inexperienced endoscopist (p<0.001). In total, 3 perforations (4%) were found. The rate of afferent loop perforation was 6.25% (1/16) for the inexperienced endoscopist and 0% (0/59) for the experienced endoscopist (p=0.053). Conclusions ERCP in patients who had undergone Billroth II gastrectomy was time consuming for the inexperienced endoscopist who should beware of the unique adverse events related to ERCP in patients with altered anatomy.